Clinical variability and probable founder effect in oculocutaneous albinism type 7. Issue 3 (6th November 2019) - Bataille, Pauline; Michaud, Vincent; Robert, Matthieu P.; Bekel, Lilia; Leclerc‐Mercier, Stéphanie; Harroche, Annie; Célérier, Charlotte; Lasseaux, Eulalie; Borgel, Delphine; Bremond‐Gignac, Dominique; Bodemer, Christine; Arveiler, Benoit; et al.
Abstract :